Numerical studies of low-dimensional quantum many-body systems. - Tan, Sisi (2014)
Exact solutions of many-body problems hold a very special and significant place in condensed matter physics, helping us to understand the behaviors of interacting particles. In this thesis, we focus our attention on study the exact solutions of two interesting many-body problems in stronglycorrelated